Theodore Boone. The abduction - Grisham, John 1955- (Hodder & Stoughton, 2012)
When his best friend disappears from her bedroom in the middle of the night, thirteen-year-old Theo uses his legal knowledge and investigative skills to chase down the truth and save April.